A device for the efficient detection of wheat seeds with waxy endosperm. Issue 5 (13th August 2019) - Morris, Craig F.; Kiszonas, Alecia M.
Abstract: Background and objectives: The development of wheat cultivars with "full waxy" grain, which lacks functional granule‐bound starch synthase genes, has zero starch amylose, and possesses unique processing properties, is highly desirable. Identification of full waxy kernels can be accomplished using differential iodine staining of starch. Findings: Endosperm starch can be easily accessed for iodine staining by cutting kernels transversely to the long axis. However, cutting by hand is slow, labor intensive and includes some safety risk. The device described herein provides for the efficient cutting of up to 48 wheat kernels simultaneously without the need for razor blades, knives, etc. The device is designed to accommodate a standard 96‐well microtiter plate to increase further the efficiency of waxy kernel detection and selection. Conclusions: The device is especially useful for detecting full waxy progeny from waxy by wild‐type crosses wherein full waxy progeny segregate in a 1:63 ratio. The device is particularly useful for developing waxy cultivars via backcross breeding. Embryo halves associated with individual distal "brush" ends that stain positive for full waxy are retained and can be saved for propagation. Significance and novelty: Waxy wheat is a novel and unique raw material. Breeding new waxy cultivars requires crossing with parents that likely are not waxy. Consequently, a safe and efficient means of detecting waxy progeny are needed. The present device fulfills this need.